Peran Konselor dalam Menangani Penderita Gangguan Jiwa Psikotik di Rumah Sakit Khusus Jiwa Soeprapto Provinsi Bengkulu - Sejati, Sugeng (Yayasan Darussalam Bengkulu, 2024)
In this study, the problems raised are How is the Role of Counselors in Handling Patients with Psychotic Mental Disorders at the Soeprapto Special Mental Hospital, Bengkulu Province. How are the counselor's obstacles in handling patients with psychotic mental disorders at the Soeprapto Special Mental Hospital, Bengkulu Province? This research uses qualitative research using descriptive methods and taking informants based on purposive sampling techniques. The results showed that the role of counselors in handling patients with psychotic mental disorders at the Soeprapto Special Mental Hospital Bengkulu includes achieving the goals of both internal and intrapersonal treatment therapy in patients with psychotic disorders, the role of counselors has been carried out well where counselors are able to empathize with patients, counselors are able to play a role in overcoming personality deficits in patients, being able to assist in making decisions, providing motivation, conducting counseling, monitoring and achieving follow-up treatment plans for psychotic mental disorder patients. Barriers to Counselors in Handling Patients with Psychotic Mental Disorders at the Soeprapto Special Mental Hospital Bengkulu include difficulties in conducting counseling due to the limited time situation, the small number of counselors and the large number of patients who need to be handled or can also get obstacles in the implementation of counseling among the lack of facilities, or it can also be from patient factors who are not willing to be assisted.